Quarter Wavelength Matching in Dielectric Resonator Bandpass Filter - Ain, M.F.; Ahmad, Z.A.; Othman, M.A.; Zubir, I.A.; Hutagalung, S.D.; Sulaiman, A. A.; Othman, A.K. (IEEE, 2010)
This paper focuses on the analysis to find suitable locations to place dielectric resonators on microstrip transmission line in order to obtain a high coupling effect. A novel design of an X-Band bandpass filter from a combination of a simple transmission line and three cylindrical dielectric resonators are used in this analysis. The three dielectric resonators are same in permittivity and radius of 60 and 2.55 mm, respectively. This analysis found that the coupling effect can be maximized by placing dielectric resonators a distance of quarter or half wavelength from each other.